A novel disposable, transnasal esophagoscope: a pilot trial of feasibility, safety, and tolerance - Chung, J. W.; Park, S.; Chung, M. J.; Park, J. Y.; Park, S. W.; Chung, J. B.; Song, S. Y. (Endoscopy, 2012)
A novel disposable transnasal esophagoscope, the E.G. Scan (IntroMedic Co. Ltd., Seoul, Korea), was developed for the evaluation of esophageal diseases while eliminating the inconvenience associated with sterilization, portability, patient monitoring, complications, and the economic burden of sedation. The feasibility, safety, and tolerability of the first version of the E.G. Scan was evaluated in this pilot study. Nasal esophagoscopy was performed successfully in 46 patients with known or suspected esophageal diseases. At least 50 % of the Z-line was visualized by the E.G. Scan in 38 (82.6 %) of 46 patients. Abnormalities were identified in 27 patients: erosive esophagitis (n = 18), Barrett’s esophagus (n = 1), esophageal varices (n = 7), and esophageal candidiasis (n = 1). Nasal pain was absent or mild in most patients, and adverse events were not observed. Further technical improvement of the E.G. Scan would increase the diagnostic usefulness in future clinical practice.